MEASUREMENTS IN A LIQUID ATOMISER SPRAY USING THE PHASE-DOPPLER PARTICLE ANALYSER (Sciences & Technology. A, exactes sciences, 2000)
Experiments have been carried out at atmospheric conditions using a water atomiser spray. A phase Doppler anemometry was used to perform the measurements of the droplets size, their velocity and concentration, and photographs were taken.  The results showed that the small particles with low turbulence occupied the central core of the jet displaying a Gaussian profile for the axial velocity component.  The large particles were defected towards the outer edges of the jet, due to their higher initial momentum, and displayed relatively high levels of turbulence. The variables measured show that their spatial distributions were nearly symmetrical about the x-axis and although the number density of the droplets is very high in the centred region, most of the pulverised liquid was present in the edges of the spray.